Guía para la administración de contratos aplicables en proyectos de obras públicas en el Hospital México - Pacheco-Jiménez, Fabián (Instituto Tecnológico de Costa Rica, 2012)
Facilities-adapting projects carried out inside main hospitals of the Caja Costarricense de Seguro Social are boosted by the very particular and all-time changing needs coming from healthcare services. The most expensive and complex healthcare facilities are built throughout projects managed by project managers coming from CCSS main offices, but the remaining infrastructure needs are fulfilled by facility’s maintenance and engineering staff. The known feebleness on conducting healthcare facilities projects in Hospital México, as well as the actual intentions for improving this matter by the foundation of the Subárea de Gestión de Proyectos de Ingeniería y Mantenimiento (Project Management Office, a division of Engineering and Maintenance Department) are the reasons why creating a project management guide is considered important for a good planning, contracting, construction and project closing. This work is focused on management of projects conducted by turnkey modality, so it is expected to be implemented as soon as possible, because there are many projects of this kind waiting to be developed. Nevertheless, future additions and improvements to this guide approach should be expected. Also, this document brings an analysis that explores the maturity of the México’s Hospital Project Office team as well as some other CCSS professionals, related with healthcare facilities project management.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2012.
Keywords: Gestión de proyectos; Administración; Contratación externa; Mantenimiento; Planificación